Giant mitral paravalvular leak closure using double transapical access - Bindo Missiroli; Antonio Totaro; Diego Magnano; Eustaquio Maria Onorato (REC: Interventional Cardiology (English Ed.), 2022)
This is the case of a 75-year-old man with heart failure (HF) due to severe aortic regurgitation caused by infective endocarditis treated with aortic and mitral bioprosthetic valve replacement. At 6 months, HF relapsed due to severe mitral paravalvular leak (PVL) regurgitation caused by a giant 33 mm x 9 mm crescent-shaped leak of medial-posterior location (2 to 5 o’clock position), with an area of 3.29 cm2 (figure 1A-E, video 1 of the supplementary data). The patient was deemed at prohibitive surgical risk, and gave his informed consent to undergo catheter based PVL closure. The procedure was performed in a hybrid operating room under general anesthesia, continuous real-time 2D/3D transesophageal echocardiography (TEE) color Doppler imaging and fluoroscopic guidance. An open surgical retrograde double transapical access (hybrid technique) was preferred due to the considerably huge size of the leak and the possible need for multiple simultaneous large devices. Through the 2 short sheaths placed at the left ventricle apex we easily passed the leak in sequence with 2 0.035-in hydrophilic guidewires that were later exchanged for 2 extra-stiff guidewires placed in the pulmonary veins (figure 2A-B). Afterwards, we implanted a 18 mm x 10 mm rectangular waist (RW) paravalvular leak device...